1994
DOI: 10.1007/bf00201043
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cytoplasmic rearrangements precede wall apposition, hypersensitive cell death and defense-related gene activation in potato/Phytophthora infestans interactions

Abstract: Abstract.We used video microscopy techniques as a tool for live examination of the dynamic aspects of plant/fungus interactions. Early, dynamic responses of epidermal midrib cells of leaves from a potato cultivar (Solanum tuberosum L. cv. Datura) carrying resistance gene R1 to Phytophthora infestans (race 1: compatible interaction, race 4: incompatible interaction) were monitored. Similar responses were observed in both types of interaction, ranging from no visible reaction of invaded plant cells to hypersensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 29 publications
6
55
0
Order By: Relevance
“…This finding is in agreement with the cytological studies of Freytag et al (1994), who observed hypersensitive reacting mesophyll cells not only in incompatible but also compatible interactions and suggested that the difference between compatibility and incompatibility is due to comparatively small quantitative difference in the number of mesophyll cells that respond hypersensitively. How these quantitative differences are determined and what the function of putative race-specific elicitors or suppressors is in this process is unclear.…”
Section: B Structure Of Oomycetous Genessupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in agreement with the cytological studies of Freytag et al (1994), who observed hypersensitive reacting mesophyll cells not only in incompatible but also compatible interactions and suggested that the difference between compatibility and incompatibility is due to comparatively small quantitative difference in the number of mesophyll cells that respond hypersensitively. How these quantitative differences are determined and what the function of putative race-specific elicitors or suppressors is in this process is unclear.…”
Section: B Structure Of Oomycetous Genessupporting
confidence: 92%
“…Characteristically, the anticlinal walls of epidermal cells are penetrated by the penetration hyphae and often the cells next to stomatal guard cells are the target sites for penetration. Hyphal structures are formed in the epidermal cell from which the mycelium grows, initially intercellularly, while intracellular haustoria are formed in the mesophyll cell layer (Coffey and Gees 1991;Freytag et al 1994).…”
Section: Disease Cycle Of Phytophthora Infestans a Asexual Lifementioning
confidence: 99%
See 1 more Smart Citation
“…The timing of these events has been precisely established using video microscopy during an incompatible interaction between Phytophthora infestans and potato. Only 26 s are necessary for plant cell collapse and death, and death of the fungus follows 20 s later (Freytag et al, 1994). Such rapid responses could make detection of intermediate steps almost impossible using fixed tissues.…”
Section: Morphologies Of Hrmentioning
confidence: 99%
“…Formation of these cell wall appositions (CWAs) or papillae is usually accompanied by a co-localised accumulation of phenolics and reactive oxygen species [2][3][4][5][6]. The complex process of sub-cellular cell wall remodelling is tightly linked to the rapid disassembly and subsequent focal reassembly of the plant cytoskeleton at fungal entry sites, which is indicative of a pathogen-triggered cell polarisation [6][7][8][9]. There has been a long-standing controversy, however, over whether CWAs function in disease resistance or facilitate the entry of fungal pathogens into host cells by providing a structural collar for the intruder.…”
Section: Introductionmentioning
confidence: 99%